Carbon quantum dot implanted graphite carbon nitride nanotubes : excellent charge separation and enhanced photocatalytic hydrogen evolution - Wang, Yang (2020)
Graphite carbon nitride (g‐C3N4) is a promising candidate for photocatalytic hydrogen production, but only shows moderate activity owing to sluggish photocarrier transfer and insufficient light absorption. Herein, carbon quantum dots (CQDs) implanted in the surface plane of g‐C3N4 nanotubes were synthesized by thermal polymerization of freeze‐dried urea and CQDs precursor. The CQD‐implanted g‐C3N4 nanotubes (CCTs) could simultaneously facilitate photoelectron transport and suppress charge recombination through their specially coupled heterogeneous interface. The electronic structure and morphology were optimized in the CCTs, contributing to greater visible light absorption and a weakened barrier of the photocarrier transfer. As a result, the CCTs exhibited efficient photocatalytic performance under light irradiation with a high H2 production rate of 3538.3 μmol g−1 h−1 and a notable quantum yield of 10.94 % at 420 nm.